Application of oral inorganic iodine in the treatment of Graves’ disease - Huang, Yixuan; Xu, Yihang; Xu, Murong; Zhao, Xiaotong; Chen, Mingwei (Frontiers in Endocrinology, 2023)
Iodine is one of the crucial trace elements for the human body and the basic raw material for the synthesis of thyroid hormones. Oral inorganic iodine includes dietary iodine and therapeutic iodine, both of which are closely associated with thyroid immunity and metabolism. Graves’ disease (GD), also known as diffuse toxic goiter, is characterized by hyperthyroidism and high iodine metabolism. Clinically, patients diagnosed with GD are often asked to limit iodine intake or even avoid iodine in their diet. The latest research has demonstrated that the interference of dietary iodine with antithyroid drug (ATD) treatment may be overestimated. In addition, as a medication for GD treatment, positive results have been obtained with the administration of inorganic iodine in patients with mild hyperthyroidism, a low thyroid autoantibody concentration, a small thyroid volume, a high iodine diet, and so on. Inorganic iodine may also be used as an alternative when side effects occur with traditional ATDs and patients still prefer conservative treatment. Inorganic iodine plays a unique role in special populations, such as pregnant or lactating patients and patients receiving tumor radiotherapy or chemotherapy, due to its low teratogenicity, blood toxicity, and bone marrow toxicity. In this review, the research progress, biological function, doses and effects, applicable populations, and specific applications of dietary iodine and therapeutic iodine are summarized to provide references for the diagnosis and treatment of GD, thus improving the quality of life of GD patients.